An Implantable Polydopamine Nanoparticle‐in‐Nanofiber Device for Synergistic Cancer Photothermal/Chemotherapy. Issue 11 (13th October 2022) - Du, Tianyi; Yang, Ting; Xu, Ling; Li, Xilin; Yang, Guang; Zhou, Shaobing
Abstract : It remains a great challenge to accurately deliver the therapeutic agents to tumor lesions to enhance the antitumor efficacy and reduce side effects. Herein, an implantable polydopamine (PDA) nanoparticle‐in‐nanofiber device for the local combination of photothermal therapy (PTT) and chemotherapy against cancer is developed. This local antitumor system can continuously release the small‐sized PDA nanoparticles with tumor targeting and superior photothermal conversion capability, which can penetrate deep into the tumor tissue. Under near‐infrared (NIR) laser irradiation, a relatively mild photothermal treatment would be implemented, which could further assist the penetration of PDA nanoparticles and promote the therapeutic agent release, achieving the synergism of localized PTT and sustainable chemotherapy. Abstract : An implantable polydopamine (PDA) nanoparticle‐in‐nanofiber device is developed for cancer therapy. When applied to peritumoral implantation, the small‐sized PDA nanoparticles with tumor targeting and superior photothermal conversion capability can be continuously released and penetrate inside the deep tumor, achieving a local combination of photothermal therapy and sustainable chemotherapy under near‐infrared (NIR) laser irradiation.